(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background : Papillary Thyroid Carcinoma (PTC) is the most common form of well differentiated thyroid cancer, and constitutes 1% of all solid tissue cancers with a female predominance and surgical intervention helps in removal of the cancer. Methods: A retrospective data analysis was done among 70 papillary thyroid carcinoma patients who had undergone radical thyroidectomy with or without selective lymph node excision in the Department of Breast and Thyroid Surgery at Shandong Provincial Hospital from 2005 to 2012. Results: The study showed a female predominance with a mean age 43.81years. 71.4% cases presented with lymphadenopathy and out of 70 patients, 16 had previous thyroid hormone dysfunction. Radical Thyroidectomy with selected lymph node excision was done in 77.1% cases and the rest had undergone only Radical Thyroidectomy. 44.3% of the tumor was <1cm in longest diameter, 58.6% cases had no lymph node metastasis and 38.6% cases had central lymph node metastasis. Mean survival after surgical management was 5.56 years with a standard deviation of 2.64 years. Only in 4 cases operative or postoperative complications were observed and in a single case we needed to perform reopen surgery. Mean hospital stay was 11days with a standard deviation of 5 days. Distant metastasis was observed only in 2 cases and correspondingly died after 1 year. Radio ablation by using radioactive Iodine (I131) was required in 5 patients and 88.6% required thyroid hormone replacement after surgery. Conclusion: So, surgical management is safe and results in an increased survival with possibility of cure in patients with papillary thyroid carcinoma. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 52-56